PsycEXTRA Dataset 2001
DOI: 10.1037/e667892007-001
|View full text |Cite
|
Sign up to set email alerts
|

The Independent Effects of Permanent Exclusion from School on the Offending Careers of Young People

Abstract: RDS is part of the Home Office. The Home Office's purpose is to build a safe, just and tolerant society in which the rights and responsibilities of individuals, families and communities are properly balanced and the protection and security of the public are maintained.RDS is also a part of the Government Statistical Service (GSS). One of the GSS aims is to inform Parliament and the citizen about the state of the nation and provide a window on the work and performance of government, allowing the impact of gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 8 publications
3
54
0
Order By: Relevance
“…9 This compares with Berridge et al (2001) who found that of 178 excluded school children who had committed crime that had been recorded, 61 had committed their first offence prior to their exclusion; 13 within the same month as their exclusion and 104 subsequent to their exclusion.…”
Section: Table (V) Permanent Exclusion By Number Of Arrests Controllimentioning
confidence: 99%
See 3 more Smart Citations
“…9 This compares with Berridge et al (2001) who found that of 178 excluded school children who had committed crime that had been recorded, 61 had committed their first offence prior to their exclusion; 13 within the same month as their exclusion and 104 subsequent to their exclusion.…”
Section: Table (V) Permanent Exclusion By Number Of Arrests Controllimentioning
confidence: 99%
“…What it does point to is that exclusion is probably one amongst a number of variables present in a young offenders life (see for example Farrington, 1994Farrington, ,1996Hayden and Martin, 1998;Sampson & Laub, 1993;Audit Commission, 1996; Social Exclusion Unit 1998; Berridge, et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many schools were labelled as failing and large numbers of young people were excluded (Osler and Starkey, 2005). Despite recent legislative changes to clarify school exclusion procedures (Berridge et al, 2001), there remain some grey areas; in particular to the use of 'unofficial' exclusions (Stirling, 1992;Social Exclusion Unit, 1998;Brodie, 1999) whereby schools discourage students from returning to a school or encourage parents to remove their children. Official guidance states that this practice is unacceptable, but it continues to take place with damaging long-term consequences for pupils and their families (Brodie, 1999).…”
Section: School Exclusion and Urban Youthmentioning
confidence: 99%